A common-sense guide to data structures and algorithms : level up your core programming skills - Wengrow, Jay (The pragmatic programmers, 2020)
Take a practical approach to data structures and algorithms, using techniques and real-world scenarios in JavaScript, Python, and Ruby that you can put into production right away. This new and revised second edition features new chapters on recursion, dynamic programming, and using Big O in your daily work. -- Provided by publisher.